Quantitative proteomics to study a small molecule targeting the loss of von Hippel–Lindau in renal cell carcinomas. Issue 4 (25th May 2017) - Bouhamdani, Nadia; Joy, Andrew; Barnett, David; Cormier, Kevin; Léger, Daniel; Chute, Ian C.; Lamarre, Simon; Ouellette, Rodney; Turcotte, Sandra
Abstract : Inactivation of the tumor suppressor gene, von Hippel–Lindau (VHL), is known to play an important role in the development of sporadic clear cell renal cell carcinomas (ccRCCs). Even if available targeted therapies for metastatic RCCs (mRCCs) have helped to improve progression‐free survival rates, they have no durable clinical response. We have previously shown the feasibility of specifically targeting the loss of VHL with the identification of a small molecule, STF‐62247. Understanding its functionality is crucial for developing durable personalized therapeutic agents differing from those available targeting hypoxia inducible factor (HIF‐) pathways. By using SILAC proteomics, we identified 755 deregulated proteins in response to STF‐62247 that were further analyzed by ingenuity pathway analysis (IPA). Bioinformatics analyses predicted alterations in 37 signaling pathways in VHL‐null cells in response to treatment. Validation of some altered pathways shows that STF‐62247's selectivity is linked to an important inhibition of mTORC1 activation in VHL‐null cells leading to protein synthesis arrest, a mechanism differing from two allosteric inhibitors Rapamycin and Everolimus. Altogether, our study identified signaling cascades driving STF‐62247 response and brings further knowledge for this molecule that shows selectivity for the loss of VHL. The use of a global SILAC approach was successful in identifying novel affected signaling pathways that could be exploited for the development of new personalized therapeutic strategies to target VHL‐inactivated RCCs. Abstract : What's new? Mutations on the tumor suppressor gene VHL are observed in most RCC cases. We previously identified a small molecule, STF‐62247 tha tis capable to kill VHL‐inactivated tumor cells. Here they used SILAC proteomics, IPA, and bioinformatics to show that STF‐62247 may arrest protein synthesis in VHL‐negative cells, while sparing normal cells. This approach also identified novel signaling pathways that could provide new, personalized therapeutic targets for ccRCC.